Model Pengabdian Masyarakat untuk Perawatan Sistem PLTS 3kWp di Kawasan Ziarah Pesisir Sayung - Kuspranoto, Abdul Haris; Ali Hasan, Ahmad; Permana Sabputra, Novantioro; Ulin Nuha ABA, Muhammad (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2026)
This community service activity aims to develop a maintenance model for a 3 kWp solar power plant (PLTS) system that is suitable for implementation in small-to-medium public service areas in Sayung, specifically the pilgrimage area of the Tomb of Sheikh Abdullah Mudzaki. The coastal setting of tidal flooding, abrasion, high humidity, and limited field access requires a more disciplined operation and maintenance (O&M) approach than typical inland locations. The methods used include synthesis of evidence from initial scans of Consensus and Scite, verification of official regional and national sources, and in-depth analysis of international standards and literature on PLTS O&M, performance monitoring, humidity/corrosion, and community-based electrification management. The synthesis results indicate that a 3 kW hybrid configuration with a 48 V battery is the most balanced option for locations requiring a steady supply when the grid is disrupted, while an on-grid system is cheaper but dependent on the grid, and an off-grid system is more independent but requires more stringent battery and charge controller design. The recommended maintenance program combines simple daily-weekly inspections by local operators, monthly-quarterly inspections by trained technicians, recording of logbook-based performance indicators, and community training emphasizing occupational safety, module cleaning, connection checks, and disturbance response. This article presents a draft maintenance schedule, training curriculum, cost estimates, monitoring-evaluation indicators, and coastal risk mitigation strategies that are ready to be adapted into a community service journal manuscript.